Antiepileptic drugs and foetal disorders: analysis of 20-year data from the pharmacovigilance center - Ji, Zejun; Nie, Jianjun; Shen, Qingli; Fu, Zhonghua (Frontiers in Pharmacology, 2025)
BackgroundFor women of childbearing age, the risks of uncontrolled epilepsy to the mother and fetus need to be balanced against the potential teratogenic effects of antiepileptic drugs (AEDs). The combined use of different types of AEDs has become a potential treatment option for the effective control of epileptic symptoms, while different studies present significant difference between the combined use of AEDs and foetal toxicity, which need a large comprehensive study to clarify the relation.ObjectiveThe study aims to analyze data from the U.S. Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) to explore the impact of monotherapy or polytherapy of AEDs on foetal and infant disorders.MethodsBayesian analysis and non-proportional methods were employed to assess the association between AED use and foetal disorders based on the FAERS database from the first quarter of 2004 to the fourth quarter of 2023. The clinical characteristics and outcome of patients were also investigated.ResultsThe study identified significant correlation between foetal disorders and the first and second generation AEDs, with RORs of 3.8 and 4.9, respectively. Valproic acid monotherapy showed the highest correlation with foetal disorders (ROR = 15.8, PRR = 16.3, IC025 = 3.8) and was uniquely associated with male reproductive toxicity. The risk of foetal disorders associated with combination therapies varied depending on the specific AEDs combination, with some increasing and others decreasing the risk compared to monotherapy.ConclusionThe analysis of the reports from FAERS database identified correlation between foetal disorders and AEDs and provided a comprehensive overview of the incidence and prognosis of different AEDs monotherapy and combination, which may provide some advice for the selection of drug for women of childbearing age.